Intramural pregnancy: A case report - Juliane Nees; Gesine Faigle-Krehl; Janina Brucker; Dagmar Leucht; Lisa Katharina Platzer; Christa Flechtenmacher; Christoph Sohn; Markus Wallwiener (Elsevier, 2020)
A 24-year-old woman, who had undergone neither fertility treatment nor uterine surgery other than a cesarean section, presented with an intramural ectopic pregnancy. A laparotomy with uterine wedge resection including the embryonic tissue was performed. The postoperative course was uneventful, with falling βHCG levels. Two months after surgery she presented again with an intrauterine pregnancy.